Toxical effects of glyphosate and acephate to the stingless bee Plebeia lucii Moure, 2004 (Hymenoptera, Apidae) - Ferreira, Lívia Maria Negrini (2021)
The conservation of terrestrial ecosystems depends largely on the conservation of pollinators, among which bees stand out. One of the probable causes for the population decline of bees is the use of pesticides, but this hypothesis has been little tested with Brazilian native bees. In tropical regions, stingless bees (Apidae, Meliponini) are the main pollinators of native plants and can be exposed to different pesticides when foraging on contaminated flowers. In this study, the susceptibility of stingless bees to the ingestion of the best-selling herbicide and insecticide in Brazil was investigated. For this, foragers of the stingless bee Plebeia lucii Moure, 2004 were orally exposed for 72 hours to food contaminated with different concentrations of the insecticide acephate or the herbicide glyphosate based on the recommended field concentrations. The number of bees alive was counted every 12 hours. Those individuals that survived to the exposure were then submitted to a bioassay to evaluate flight recovery ability. The data on the number of bees alive every 12 hours was analyzed through a survival analysis, which determined the survival probability and median lethal time (LT 50) per treatment. The mortality of bees after 72 hours was analyzed through a Probit regression, which estimated the concentration-mortality response and determined the lethal concentrations at 50% and 90% (LC50 and LC90, respectively). The flight recovery ability was analyzed through a generalized linear model (GLM). After 72 hours, the survival of bees and LT50 was negatively affected by the ingestion of acephate (ꭕ2=62.4, df=6, p<0.001) and glyphosate (ꭕ2=196, df=6, p<0.001). The acephate LC50 was 3.639 mg a.i./L and the LC90 was 8.38 mg a.i./L. The glyphosate LC50 was 17,000 mg a.i./L and the LC90 was 41,749 mg a.i./L. Both LC50 and LC90 differed between pesticides, based on the 95% confidence interval. The ingestion of acephate (ꭕ2=143.29, df=110, p=0.004) or glyphosate (ꭕ2=50.682, df=60, p<0.001) affected the bee’s flight recovery ability. The proportion of bees that were unable to recover flight was higher for foragers treated with the highest concentrations of acephate (ꭕ2=35.272, df=22, p=0.017) or glyphosate (F(2,12)=6.688, p=0.012) tested here. The proportion of bees that were able to recover flight and fly towards the light did not differ within acephate (ꭕ2=29.283, df=22, p=0.051) nor glyphosate (F(2,12)=3.379, p=0.069) treatments. Our results with P. lucii indicated that: higher concentrations of these pesticides reduced the lifespan of foragers; higher concentrations of both agrochemicals increased the mortality; acephate was more toxic to P. lucii than glyphosate; higher concentrations of these pesticides impaired flight ability. This shows that P. lucii is susceptible to these pesticides. Our study provides additional information on the detrimental effects of pesticides on native stingless bees and contribute to the knowledge needed to guide conservation strategies of these important pollinators. Keywords: Bee decline. Herbicide. Insecticide. Meliponini. Pollinator conservation.